Virtual Educational Spaces and Autonomous Learning of the English Language in Pedagogical Higher Education in Juliaca, 2024 - Orihuela-Sanabria, Alberto Salvador; Mamani-Flores, Adderly; Apaza-Ticona, Jorge; Alanoca-Arocutipa, Vicente; Calderón-Torres, Alfredo; Flores-Mamani, Emilio; Inquilla-Mamani, Juan (Journal of Ecohumanism, 2024)
This study evaluated the impact of virtual educational environments on the autonomous learning of English in pedagogical higher education students in Juliaca, specifically at the Cenit Galeaza Institute of Public Pedagogical Higher Education (IESPP), during the year 2024. A quantitative approach with a longitudinal correlational descriptive design was used. The population was made up of 256 students from the ten academic semesters, from which a representative sample of 157 participants was selected through simple random probability sampling. The data analysis, carried out using SPSS software, showed that virtual environments contribute significantly to the strengthening of autonomous learning. This was reflected in the adequate reliability of the measuring instrument, with a Cronbach’s alpha coefficient of 0.768. Likewise, it was observed that these tools enhance the development of cognitive skills, encourage academic habits and promote positive attitudes towards learning. The results underscore the relevance of virtual educational spaces as effective resources to improve academic performance and autonomy in English language learning. It is recommended to continue implementing these platforms in the institution, as well as in similar educational contexts, in order to confirm and expand the findings obtained. These initiatives would strengthen the development of essential competences for the training of future teachers and optimize the teaching of foreign languages in the pedagogical field.